Process of care and assistance quality to women in labor with greater access to social goods - Adriana Cristina D’Ornelas (Einstein (São Paulo), 2009)
Objective: This study aimed at analyzing the process of care and the quality of vaginal delivery assistance in women with greater access to social goods, in a large private hospital in São Paulo, comparing the delivery room with delivery suites. Methods: Cross-sectional and retrospective study, using random sampling of 395 medical charts. Rresults: In the delivery room, labor lasted two hours with the use of oxytocin (56.3%), double-block anesthesia (76.3%) and right mediolateral episiotomy (67.7%). At the delivery suites, duration of labor was over ten hours (27.1%), the use of prostaglandin (8.6%), anesthesia by double block technique (61.4%), no anesthesia in 10%, midline episiotomy in 48.6%. Gestational age over 37 weeks (92.3%), birth weight of 3 kg or more (71.4%) and 93.5% were referred to the normal nursery. Cconclusion: The results indicated good quality of care during hospitalization and development of delivery, both in the delivery room and in the delivery suites.